Electronically coupled hybrid structures by graphene oxide directed self-assembly of Cu2−xS nanocrystals1. Issue 15 (21st April 2015) - Neyshtadt, Shany; Kriegel, Ilka; Rodríguez-Fernández, Jessica; Hug, Stephan; Lotsch, Bettina; Da Como, Enrico
<x xml:space="preserve">Abstract</x> Self-assembly of plasmonic Cu2−xS nanocrystals and graphene oxide via macroemulsion route yields electronically coupled hybrid material.